2005
DOI: 10.1017/s1431927605505385
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Ribbon Borides in a Ti-44Al-4Nb-4Zr-1B Alloy

Abstract: There has been considerable interest in the addition of beta-stabilizing elements, such as Nb and Zr to titanium aluminide alloys because the beta phase imparts improved ductility and toughness [1]. The alloys are typically produced by casting, and to retain high strength it is imperative to refine the as-cast grain structure. This is typically achieved by the addition of B, but there is still some controversy about the refinement mechanism. In our work we are attempting to address this issue by studying the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…On the other hand, although B.J. Inkson et al 15 revealed the orientation relationship between TiB 2 and B2, and U. Kitkamthorn et al 16,17 examined the orientation relationship between TiB (B f ) and B2, the orientation relationship between TiB (B27) and B2 has not been reported. (TiB phase has two kinds of structures, Bf and B27.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, although B.J. Inkson et al 15 revealed the orientation relationship between TiB 2 and B2, and U. Kitkamthorn et al 16,17 examined the orientation relationship between TiB (B f ) and B2, the orientation relationship between TiB (B27) and B2 has not been reported. (TiB phase has two kinds of structures, Bf and B27.…”
Section: Introductionmentioning
confidence: 99%